Damage to vascular endothelium in the treatment of acute leukemia: in vitro study - Yu A Romanov; A M Chervontseva; V G Savchenko (Терапевтический архив, 2004)
Aim. Cytostatic drugs used in the treatment of hemopoietic malignancies affect cells of other organs and systems, vascular endothelium, in particular. This leads to cardiovascular complications. We studied effects of some drugs and their combinations on cultured human endothelial cells (EC). Material and methods. Primary culture of umbilical human vein EC was used in the study. Cytosinearabinoside (cytozar, alexan, cytarabin) and daunorubicin were added in concentration from 1 ng/ml to 1 mg/ml; the action of the drugs was assessed by morphology of the cells, their viability, inclusion of bromodesoxyuridine by means of cloning, immunohistochemistry and flow cytofluorimetry. Results. It is shown that in a wide range of concentrations cytosinearabinoside and daunorubicine cause specific structural-functional changes in the cells related to cytostatic and cytotoxic effects. Conclusion. The data of the study confirm that cardiovascular complications in the course of acute leukemia treatment are resultant from systemic damage to vascular endothelium.